Hydrogen-based membrane biofilm reactor for tetracycline removal: biodegradation, transformation products, and microbial community - Taskan, Banu; Hanay, Ozge; Taskan, Ergin; Erdem, Mehmet; Hasar, Halil (Springer Heidelberg, 2016)
Tetracycline (TC) in aqueous environment could be reductively degraded by using a hydrogen-based membrane biofilm reactor (H-2-MBfR) under denitrifying conditions as it provides an appropriate environment for the antibiotic-degrading bacteria in biofilm communities. This study evaluates the performance of H-2-MBfR for simultaneous removal of nitrate and TC, formation of degradation products of TC, and community analysis of the biofilm grown on the gas-permeable hollow fiber membranes. Hence, a H-2-MBfR receiving approximately 20 mg N/l nitrate and 0.5 mg/l TC was operated under different H-2 pressures, hydraulic retention times (HRTs), and influent TC concentrations in order to provide various nitrate and TC loadings. The results showed that H-2-MBfR accomplished successfully the degradation of TC, and it reached TC removal of 80-95 % at 10 h of HRT and 6 psi (0.41 atm) of H-2 gas pressure. TC degradation took placed at increased HRT and H-2 pressures while nitrate was the preferred electron acceptor for most of the electrons generated from H-2 oxidation used for denitrification. The transformation products of TC were found at part per billion levels through all the experiments, and the concentrations decreased with the increasing HRT regardless of H-2 pressure. Analyses from clone library showed that the microbial diversity at the optimal conditions was higher than that at the other periods. The dominant species were revealed to be Betaproteobacteria, Acidovorax caeni, and Alicycliphilus denitrificans.
Keywords: Tetracycline; H-2 gas; Membrane biofilm reactor; Biological degradation; Microbial community; Transformation products